STRATEGI KEPALA MADRASAH DALAM MENINGKATKAN KUALITAS PENDIDIKAN DI MTs DDI NURUSSALAM LASSA-LASSA KABUPATEN GOWA: STRATEGI KEPALA MADRASAH DALAM MENINGKATKAN KUALITAS PENDIDIKAN - Marpiansyah, M. Jusran; Bunyamin, Andi; M. Akil; Mustamin; Wahab, Abdul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study explores the principal’s strategies in improving the quality of education at MTs DDI Nurussalam Lassa-Lassa, Gowa Regency. The background of this research highlights the critical role of leadership in addressing educational challenges such as limited infrastructure, low teacher participation in training, and insufficient academic supervision. School principals are expected to demonstrate effective leadership and managerial competencies to foster positive change within the institution. Using a qualitative approach and case study method, this research investigates the principal’s involvement in planning, implementing, supervising, and evaluating educational activities. Data were collected through observation, interviews, and documentation. Strategies include teacher empowerment, infrastructure management, supervision systems, and the development of a collaborative and innovative school culture. The findings indicate that effective leadership significantly enhances the quality of teaching and learning, teacher motivation, and public trust in the school. With the right strategies, the school principal is able to overcome obstacles and establish a sustainable and high-quality educational environment.